Aggression and violence in adolescence - Marcus, Robert F., 1943- (Cambridge University Press, 2007)
Using confidential self-report surveys and official crime statistics, this book describes variations in aggression and violence during adolescence over time and by grade, gender, and race. Early clues present in childhood to later serious violence in adolescence are identified in longitudinal research studies. Current personality and situational influences that either increase or decrease risk for aggression or violence are reviewed. Aggression and violence in adolescent dating relationships is explained in relation to normal development and subject to both variation in partner and relationship differences. This book describes and suggests prevention programs directed at all children, children at risk, and those adolescents that are unfortunately already violent.